(3cJGH CSQGQ GdQLGds - (3LGdjfhSs
(3ChdgG (B:s
(3GdMeO ddg QH GdYGdejf CeG HYO aESHH hVY gPG GdcJGH GdedbH CSQGQ GdQLGd Cfg HdZfG Cf bSWGS GdbgQeGf s
(3BNQgG (B:s
(3GdCOhjI GdJi JHZV GdfSGA Edi GdQLGd MJi Cf GdQLd dGjMH Cf jQi GdfSGA aVdkG Cf jLGeYgf hjfXQ Edjgf Je CSQGQ GdQLGd s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdQGHYs
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI jhJG s
Keywords: (3GdWHs